A shallow cable with a tuned mass-high damping rubber damper. Issue 1 (March 2023) - Zhang, Zheng; Liu, Pengan; Li, Changzhao
Tuned mass-high damping rubber damper (TM-HDR-D), as a high-efficiency damper, has great practical feasibility and good application prospect for cable vibration mitigation. To investigate the effect of TM-HDR-D on the cable dynamics, a refined model which considers the cable sag effect is established via complex modal method. Then, based on this model, the influence of cable sag and the stiffness, location, loss factor, and mass of the TM-HDR-D on the cable dynamics is systematically investigated. Meanwhile, the multi-mode damping effect of TM-HDR-D is also analyzed. Results show that TM-HDR-D can significantly increase the additional damping of the system. The cable sag only affects the first-order modal damping, and the effect of TM-HDR-D is significantly affected by its frequency, loss factor, and installation position. Improving the mass of the damper can improve the damping effect. Reasonable selection of damper tuning frequency can achieve multi-order modal damping enhancement.